KEBIJAKAN PENDIDIKAN INDONESIA: KEBIJAKAN BERBASIS RISET - Joni Herri, Sar (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2015)
Technological achievements of the 21th century has affected all aspects of social, political, cultural, Educational, and religious. In the field of education, education reform must be done in order to remain relevant to contemporary circumstances. Therefore, vigorous research activities carried out by the government, namely the Ministry of Education and Culture, education practitioners, students and professors of the universities, and teachers at the school. But unfortunately, most of the results of these studies are still struggling in the micro range. Within the framework of basic education in the Graduate School of Education University of Indonesia. Since 2006 until 2013, virtually no research has "dared" the theme in the context of the macro, such as education policy, problems of primary education access and mother tongue. Tens and even hundreds thesis carefully made by students just become dusty piles of paper in the library. Process research and policy education is still being on their own. The involvement of each party that conducts research and policy makers have not resulted in a synergy that can contribute to the quality of national education. In the era of education based on science, research results can be used as an important basis in education policy.